2020
DOI: 10.2478/popets-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

NoMoATS: Towards Automatic Detection of Mobile Tracking

Abstract: Today’s mobile apps employ third-party advertising and tracking (A&T) libraries, which may pose a threat to privacy. State-of-the-art detects and blocks outgoing A&T HTTP/S requests by using manually curated filter lists (e.g. EasyList), and recently, using machine learning approaches. The major bottleneck of both filter lists and classifiers is that they rely on experts and the community to inspect traffic and manually create filter list rules that can then be used to block traffic or label ground tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…The newly selected candidate apps, which we call the obfuscation apps (note that in this work, we interchangeably use both 'newly suggested apps' and 'obfuscation apps'), are selected (and run for specific amount of time, as described in Eq. 23, (24), and (25)) from apps categories Φ j , j = 1, ..., φ other than the private category Φ p ; Φ p is considered private by users that they want to protect. The newly suggested set S o comprises those apps with highest similarity to the existing set of apps i.e.…”
Section: Protecting Sensitive Profiling Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…The newly selected candidate apps, which we call the obfuscation apps (note that in this work, we interchangeably use both 'newly suggested apps' and 'obfuscation apps'), are selected (and run for specific amount of time, as described in Eq. 23, (24), and (25)) from apps categories Φ j , j = 1, ..., φ other than the private category Φ p ; Φ p is considered private by users that they want to protect. The newly suggested set S o comprises those apps with highest similarity to the existing set of apps i.e.…”
Section: Protecting Sensitive Profiling Interestsmentioning
confidence: 99%
“…s.t. constants: (13), (14), (15), (17), (24). An important challenge to solve this optimisation problem is to know user's temporal behavior as a combined activity of 'Web & App' i.e.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…direct and indirect (inferred) leakage, have been investigated extensively in literature, e.g. [1], [43], [44], [45], including third party ad tracking and visiting [46], [47], [48], [49]. These studies have shown the prevalence of tracking on both web and mobile environments and demonstrate the possibility of inferring user's PII, such as age, gender, relationship status, email address, etc.…”
Section: Related Workmentioning
confidence: 99%
“…direct and inferred leakage), have been examined extensively in literature, e.g. [10], [97], including third party ad tracking and visiting [98], [99].…”
Section: Third-party Trackingmentioning
confidence: 99%